2019
DOI: 10.1272/jnms.jnms.2018_86-404
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of Alveolar Rhabdomyosarcoma Cells in the Ascites of a 50-Year-Old Woman: Diagnostic Challenges and Literature Review

Abstract: Alveolar rhabdomyosarcoma (ARMS) is a nonepithelial tumor with skeletal muscle differentiation and typically affects adolescents and young adults. The cytological features of ARMS in body fluid have not been well characterized, which complicates diagnosis. Here, we describe the cytological features of ARMS in the ascites of a 50-year-old woman with an intra-abdominal mass and abundant ascites. Aspiration cytology of ascitic fluid revealed numerous small discohesive round cells with mild nuclear atypia and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Prior case reports have suggested that ARMS in effusion specimens present primarily as discohesive, single cells 14,15 . Other studies have suggested that ARMS cells involving effusion samples may be difficult to distinguish from reactive mesothelial cells, 16 and mesothelial‐type features such as cellular “windows” and cannibalism are occasionally seen in ARMS 17 . Hemophagocytosis in neoplastic cells, mimicking monocyte‐histiocyte proliferative disorders, has also been reported, 18 though this feature was not seen in our current specimen.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Prior case reports have suggested that ARMS in effusion specimens present primarily as discohesive, single cells 14,15 . Other studies have suggested that ARMS cells involving effusion samples may be difficult to distinguish from reactive mesothelial cells, 16 and mesothelial‐type features such as cellular “windows” and cannibalism are occasionally seen in ARMS 17 . Hemophagocytosis in neoplastic cells, mimicking monocyte‐histiocyte proliferative disorders, has also been reported, 18 though this feature was not seen in our current specimen.…”
Section: Discussionmentioning
confidence: 44%
“…14,15 Other studies have suggested that ARMS cells involving effusion samples may be difficult to distinguish from reactive mesothelial cells, 16 and mesothelial-type features such as cellular "windows" and cannibalism are occasionally seen in ARMS. 17 Hemophagocytosis in neoplastic cells, mimicking monocyte-histiocyte proliferative disorders, has also been reported, 18 though this feature was not seen in our current specimen. In another recent case series assessing the cytologic features of various sarcomas involving body cavity fluids, 3 showed that while 100% of cases were diffusely positive for desmin, myogenin, and MYOD1 (confirming the diagnosis of rhabdomyosarcoma), 54% were also positive for at least one cytokeratin, a potential pitfall.…”
Section: Case Reportmentioning
confidence: 43%
“…The incidence of RMS is 5.4 per million total population younger than 15 years, and this tumor arises from various sites, most frequently the head and neck, extremities, and genitourinary tract [35, 38]. RMS is further subclassified as embryonal, alveolar, and pleomorphic types and develops predominately in younger children, older children/adolescents, and older adults, respectively [23, 36, 39-41].…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…Of interest, Nelson et al [7] described the potential diagnostic pitfall of misinterpreting tumor cells as mesothelial cells, especially since the neoplastic cells can be admixed with reactive mesothelial cells. Additional studies have also discussed the overlapping features of RMS cells and reactive mesothelial cells [37, 41]. Overall, in comparison to reactive mesothelial cells, RMS cells are smaller, have more frequently eccentrically placed, slightly larger hyperchromatic nuclei, possible nucleoli, and less cytoplasm [7].…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
See 1 more Smart Citation